The Application of Realistic Mathematic Education (RME) Increasing Students' Mathematics Learning Outcomes in Class VI Social Materials SDN 101878 Kanan I Tanjung Morawa - Ainur Sakinah; Nuraini Lubis; Paini (International Journal of Educational Research Excellence (IJERE), 2022)
This research started from the fact that many fifth grade students of SD 101878 Kanan I, Tanjung Morawa, had difficulty understanding fractions, especially in learning to recognize fractions. This is because the teacher does not provide fractional learning realistically in accordance with the student's concrete situation. One solution to overcome this problem is to use the RME approach. RME is one approach to learning mathematics that is oriented to everyday experiences. This research is a classroom action research conducted in two cycles. classroom action research that forms a cycle, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. Collecting data in this study using observation, documentation and test techniques.